1.8k views
5 votes
Given: LN⊥KM,KL≅ML Prove: ΔKLN≅ΔMLN

Given: LN⊥KM,KL≅ML Prove: ΔKLN≅ΔMLN-example-1

1 Answer

3 votes

Answer:

The Proof is given below.

Explanation:

Given:

LN⊥KM,

KL≅ML

To Prove:

ΔKLN≅ΔMLN

Proof:

In Δ KLN and Δ MLN

KL ≅ ML ....……….{Given i.e Hypotenuse }

LN ≅ LN …………..{Reflexive Property}

∠ LNK ≅ ∠ LNM ……….{ LN ⊥ KM i.e Measure of each angle is 90° given}

Δ KLN ≅ Δ MLN ….{By Hypotenuse Leg Theorem} ....Proved

User Pokero
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.